PERAN DAN DINAMIKA KELOMPOK DALAM KEHIDUPAN SOSIAL EKONOMI NELAYAN (Studi Kasus di Desa Citemu Kecamatan Mundu Kabupaten Cirebon) - Syipah Khoeril Mala (UIN Siber Syekh Nurjati Cirebon, 2016)
The coastal communities are formed in different social groups. Social groups of fishermen have a role as group dynamics in social and economic life . This study aims to determine and describe the role and dynamics of fishing groups in social and economic life in fishing communities. This study used a qualitative approach by observation method, interview and literature study. The results indicate that the social group of fishermen in the dynamic of community of Citemu village in its role as a forum to gain access economic or carrying capacity, as a medium for self-actualization, as a place for the purpose, and as a medium to gain access to the power of the government or the company.Key words: Group dynamic, fisherman, social roles